Mengukur Kepuasan Masyarakat Pada Program CSR di Desa Kertajaya: Sebuah Analisis Menggunakan Metode Sustainability Compass - Wahyu Eko Widodo; Sri Noor Cholidah; Anis Putri Isnaeni; Kamto Tri Wibowo; Erick Abriandi (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2019)
Kertajaya Village has a high unemployment problem. But the potential for growth is quite large because it is in the Ring I area of PT. Pertamina (Persero) TBBM Bandung. Correct if the CSR program called Kertajaya Creative Destination becomes a priority agenda. CSR programs must run well. Laterally with the main objectives of the Sustainability Development Goals (SDGs). This paper also describes the CSR program that has been consecutively in Kertajaya Village. The steps taken in unraveling the success of CSR programs through the analysis of the community satisfaction index. This paper finds that CSR programs that are running are considered positive by the community. Showed by the survey conducted for 18 beneficiaries had a final score of 3.48. This assessment is included in the “very good” category. This valuation is applied to 8 programs that have been successively, including the bag craftsmen group, the Eco-Blinder artisans group, West Bandung creative economy forum, Balai Seni Barli (BSB) tourism, Kertajaya youth clubs (karang taruna), Kertajaya culinary producers, Turban groups, and Masebajaya groups. After being analyzed using the sustainability compass method, there are two groups that need to be improved by the program, namely the Turban and Masebajaya groups. The sustainability compass method is used as an offer to stakeholders to follow up on the input generated from this paper. The main schemes studied are nature, economy, society, and well-being. As a dealectically, the main purpose of this paper is not as a discourse but rather a blue print of policy changes.Desa Kertajaya memiliki masalah pengangguran cukup tinggi. Namun potensi untuk berkembang cukup besar karena ada di wilayah Ring I PT. Pertamina (Persero) TBBM Bandung. Tepat jika program CSR bernama Kertajaya Creative Destination menjadi agenda prioritas. Program CSR harus berjalan dengan baik. Seiring dengan tujuan utama sasaran Sustainability Development Goals (SDGs). Paper ini juga mengurai program CSR yang sudah berjalan di Desa Kertajaya. Langkah yang ditempuh dalam mengurai keberhasilan program CSR melalui analisis indeks kepuasan masyarakat. Tulisan ini menemukan program CSR yang berjalan dinilai positif oleh masyarakat. Terbukti dengan survei yang dilakukan kepada 18 orang penerima manfaat memiliki skor akhir 3.48. Nilai ini masuk ke dalam kategori “sangat baik”. Penilaian ini diberlakukan kepada 8 program yang sudah berjalan, antara lain kelompok pengrajin tas, kelompok pengrajin Eco-Blinder, forum ekonomi kreatif Bandung Barat, wisata Balai Seni Barli (BSB), karang taruna Kertajaya, Produsen kuliner Kertajaya, kelompok Turban, dan kelompok Masebajaya. Setelah dianalisis menggunakan metode sustainability compass, ada dua kelompok yang perlu ditingkatkan program, yaitu kelompok Turban dan Masebajaya. Metode sustainability compass digunakan sebagai tawaran kepada stakeholder untuk menindaklanjuti masukan yang dihasilkan dari tulisan ini. Dengan skema utama yang dikaji adalah nature, economy, society, dan well-being. Secara dealektis, tujuan utama paper ini bukan sebagai diskursus tapi lebih tepat menjadi catatan blue print perubahan kebijakan.